An IEEE 802.11 energy efficient mechanism for continuous media applications - Bernardo, Vitor (2014)
The widespread deployment of wireless mobile communications enables an almost permanent usage of portable devices, which imposes high demands on the battery of these devices. Indeed, battery lifetime is becoming one the most critical factors on the end-users satisfaction when using wireless communications. In this work, the optimized power save algorithm for continuous media applications (OPAMA) is proposed, aiming at enhancing the energy efficiency on end-users devices. By combining the application specific requirements with data aggregation techniques, OPAMA improves the standard IEEE 802.11 legacy Power Save Mode (PSM) performance. The algorithm uses the feedback on the end-user expected quality to establish a proper tradeoff between energy consumption and application performance. OPAMA was assessed in the OMNeT++ simulator, using real traces of variable bitrate video streaming applications, and in a real testbed employing a novel methodology intended to perform an accurate evaluation concerning video Quality of Experience (QoE) perceived by the end-users. The results revealed the OPAMA capability to enhance energy efficiency without degrading the end-user observed QoE, achieving savings up to 44% when compared with the IEEE 802.11 legacy PSM.